Muscle Extracellular Matrix Scaffold Is a Multipotent Environment - Aulino, Paola (Int J Med Sci, 2015)
The multipotency of scaffolds is a new concept. Skeletal muscle acellular scaffolds (MAS) implanted at the interface of Tibialis Anterior/tibial bone and masseter muscle/mandible bone in a murine model were colonized by muscle cells near the host muscle and by bone-cartilaginous tissues near the host bone, thus highlighting the importance of the environment in directing cell homing and differentiation. These results unveil the multipotency of MAS and point to the potential of this new technique as a valuable tool in musculo-skeletal tissue regeneration.